Implikasi Hukum Keterangan Palsu yang diberikan oleh Panghadap Terhadap Pejabat Pembuat Akta Tanah - Ade Putra F Sumbara; Rasji, Rasji (UNES Law Review, 2024)
The legal implication for the Land Deed Official on the false statement given by the confrontant is the potential for PPAT to participate in the criminal act of making an authentic deed based on false information or document forgery. However, with the use of the analysis of Article 1365 of the Civil Code and regulations governing the duties functions and authority of PPAT. Then the PPAT has no material obligation in examining to prove the authenticity of the documents or information presented to him. If the formal examination has proven that there is no indication of document forgery and the PPAT makes an authentic letter to the applicant. Then the elements of criminal and unlawful acts are not included in the acts committed by the PPAT in making an authentic deed based on false information provided by the public/applicant to the PPAT.